Crossmedia Flows of Documentary Images and the Transnational Communicative Figuration Surrounding Gestational Surrogacy in India. (December 2018) - Schneider, Nadja-Christina
The article is based on the assumption that documentary films are an important ' channel of mediation' (Strathern, 2002, Journal of Molecular Biology, 319 (4), 985–993) that helps make visible the changing configurations of family, kinship and social reproduction. It further assumes that documentary images of egg donors, medical procedures, fertility clinics, delivery or labouring bodies of surrogates, and handing over of a 'commodified' newborn baby to the commissioning parents effectively convey the repercussions that gestational surrogacy has for all the medicalised bodies which are involved in the transnational processes of reproduction. Widely circulated and received documentaries such as Google Baby (2009), House of Surrogates (2013), Ma Na Sapna: A Mother's Dream (2013) or Can We See the Baby Bump Please? (2013) often function as a starting point and major reference for the debate about this complex issue. But while academic or journalistic articles mostly refer to individual films and on the theme in focus, the different context(s) of the medium itself are less reflected upon. Documentary filmmaking is of course always situated in a specific sociopolitical context, and this in turn shapes the way in which the visual medium make us, as non-experts, see and learn. It also forms the basis of our quest for more knowledge and better understanding, that is, in this case of the transnational entanglements in the field of assisted reproductive technologies. In addition to that, like any other medium or media-related practice today, documentary filmmaking is also embedded in profoundly transformed media environments, networks and communicative practices. In order to understand how information and knowledge about split parenthood and gestational surrogacy is mediated to transnational audiences and framed in public discussions, it is thus necessary to shed light on the interconnectedness of different media forms and framings through which the communication around this complex topic has formed. Instead of a close reading of selected documentaries, the article therefore attempts to trace and contextualise the crossmedial and translocal itineraries of three key images and central tropes that have influenced the framing of transnational reproduction and gestational surrogacy in India significantly: (a) the medical authority-cum-media actor (i.e., internationally well-known fertility expert and doctor in charge, Dr Nayana Patel), (b) the surrogacy hostels and dormitories (i.e., the central symbol of constant surveillance and control of surrogates) and (c) the metaphor of 'rented/hired wombs' (i.e., the notion of a passive provision of body parts and understanding of gestational surrogacy as active labour).